Chemical Priming by Isothiocyanates Protects Against Intoxication by Products of the Mustard Oil Bomb - Ferber, Elena; Gerhards, Julian; Sauer, Miriam; Krischke, Markus; Dittrich, Marcus T.; Müller, Tobias; Berger, Susanne; Fekete, Agnes; Mueller, Martin J. (Frontiers in Plant Science, 2020)
In Brassicaceae, tissue damage triggers the mustard oil bomb i.e. activates the degradation of glucosinolates by myrosinases leading to a rapid accumulation of isothiocyanates at the site of damage. Isothiocyanates are reactive electrophilic species (RES) that covalently bind to thiols in proteins and glutathione, a process that is not only toxic to herbivores and microbes but can also cause cell death of healthy plant tissues. Subtoxic isothiocyanate concentrations, likely occurring in the vicinity of disrupted tissue, can induce transcriptional reprogramming in intact plant cells. Glutathione depletion by RES leading to breakdown of the redox potential has been proposed as a central and common RES signal transduction mechanism. However, transcriptome analyses of Arabidopsis plants exposed to subtoxic concentrations of sulforaphane revealed regulation of hundreds of genes without depletion of the cellular glutathione pool. Heat shock genes were among the most highly up-regulated genes and this response was found to be dependent on the canonical heat shock factors A1 (HSFA1). HSFA1-deficient plants were more sensitive to isothiocyanates than wild type plants. Moreover, pretreatment of Arabidopsis seedlings with subtoxic concentrations of isothiocyanates increased resistance towards toxic levels of isothiocyanates and, hence, may reduce the autotoxicity of the mustard oil bomb by inducing cell protection mechanisms.